Effects of using self-explanation on a web-based Chinese sentence-learning system. Issue 1 (17th February 2017) - Chang, Jia-Wei; Lee, Ming-Che; Su, Chien-Yuan; Wang, Tzone-I
Abstract : Chinese as a foreign language (CFL) learners generally encounter difficulty in using some special rules of Chinese grammar because such grammar points do not exist in their native languages. CFL learners require an effective learning strategy to assist them in acquiring a greater understanding of Chinese grammar. Thus, we integrated a self-explanation strategy into a Chinese-learning system. Specifically, the system includes self-explanation prompts, instructional feedback, and remedial learning materials. The aim of this study was to determine the effects of using a self-explanation strategy on Chinese sentence learning in a computer-assisted language learning environment. The participants were assigned to an experiment group with self-explanation instruction and a control group without self-explanation to practice Chinese grammar points. Learning performance, including grammar tests and cognitive loads, was measured. The results showed higher learning outcomes for Chinese grammar and sentence structure in the self-explanation group. Furthermore, no significant difference in cognitive load was observed between the two groups. Implications for using self-explanation in computer-assisted language learning are discussed.